Effect of short term changes in blood glucose on visual pathway function in insulin dependent diabetes. Issue 1 (January 1995) - Hardy, K J; Scase, M O; Foster, D H; Scarpello, J H
Abstract : BACKGROUND--Visual pathway function is abnormal in patients with insulin dependent diabetes mellitus (IDDM) without retinopathy, yet the mechanism underlying this abnormality is unknown. It is hypothesised that short term changes in blood glucose level affect visual pathway function in IDDM. METHODS--Colour discrimination was measured in 10 uncomplicated aretinopathic IDDM patients during hyperinsulinaemic clamp, with the Farnsworth Munsell 100 hue test (100 hue test). After stable euglycaemia, patients were made hyperglycaemic (14 mmol/l), maintained euglycaemic (5 mmol/l), and rendered hypoglycaemic (2.5 mmol/l), in random order, on separate occasions at least 1 week apart. RESULTS--Short term (1-2 hours) changes in blood glucose did not affect colour discrimination: mean (SD) 100 hue error score at 2.5 mmol/l was 34 (22) compared with 35 (33) at 5 mmol/l, and 39 (28) at 14 mmol/l. CONCLUSION--These data suggest that short term (1-2 hours) changes in blood glucose are not the mechanism for visual pathway dysfunction in aretinopathic IDDM patients.